Open mesh repair, is still a standard technique for incisional hernia: a comparision study between sublay and onlay technique in the era of laparoscopy - Lamani, Yamanur P.; Halbhavi, Subhash N.; Goudar, Bheemangowda V.; Kalaburgi, Eshwar B.; Y. C., Veerabhadra Gowd (International Surgery Journal, 2018)
Background: Incisional hernia (IH) remains a very frequent postoperative complication and common hernias in middle aged population more commonly in females. The two techniques most frequently used are the onlay repair and sublay repair. Various studies have been conducted to compare the advantages and disadvantages of sublay and onlay mesh repair in incisional hernia and the superiority of sublay mesh repair. These studies whether they hold good for the population is a pertinent question. In view of this, author need to study the appropriate surgical techniques sublay versus onlay repair in the set up. Methods: Author conducted randomized comparative study of 100 patients having incisional hernia admitted to various surgical units of SNMC and HSK Hospital, Bagalkot during the period December 2014 to June 2016. Results: In present study of 100 cases, females have more incidence of incisional hernias than males. In onlay technique seroma formation was found in 72% of patients postoperatively and 4% in sublay technique. Surgical site infection (SSIN) was noticed in 8% of sublay technique whereas 12% in onlay technique. There is no recurrence in sublay group whereas onlay had 12% recurrence. Conclusions: Sublay technique is superior to onlay concerning the hospital stay, complications and recurrence.